Pemenuhan Layanan Pendidikan bagi Peserta Didik Penghayat Kepercayaan (Indigenous Religion) di DIY(Studi Kasus Kabupaten Gunungkidul pada tahun 2022) - Tri Noviana (SMARTINDO, 2023)
This research was conducted to determine the impact of the Constitutional Court Decision No.97 of 2016 and Ministerial Regulation No. 27 of 2016 concerning educational services for followers of faith in Gunungkidul. The problem of discrimination experienced by adherents continuesto occur. This study used a simple random sampling methodology in addition to a participatory research survey by distributing 292 questionnairesto 292 people who had changed the KTP column for adherents of belief. The results of this study illustrate that after more than 4 years of Permendikbud No. 27 of 2016 issued in the Gunungkidul district, no one has access to internal education services. So that the provincial anddistrict governments still have to work hard to socialize widely, as well as implementing and overseeing Permendikbud No. 27 of 2016 and Guidelines for the Implementation of Education Services for Belief in God Almighty in the Education Unit. It is appropriate for the provincialand district governmentstogether with the spiritual organizations at the provincial and district levelsto carry out data collection on internal studentsand to prepare natural educators for internal students for the sake of good educational public services for adherents.